Penerapan Pembelajaran Berdiferensiasi dengan Model PBL untuk Meningkatkan Kemampuan Numerasi Matematika Kelas V-B SD Supriyadi - Prasetyo, Ade Salim; Nuvitalia, Duwi; Setyaningsih, Ariani Nur; Nugroho, Aryo Andri (Indo-MathEdu Intellectuals Journal, 2024)
As a foundation of mathematics education, students' numeracy skills are taken into consideration. By using the PBL differentiated learning model, this project aims to improve children's numeracy skills at Supriyadi Elementary School. This research was conducted in the 2023–2024 academic year and is categorized as classroom action research (CAR). The subjects of the study where 26 students from class V-B. Data were collected using written tests and direct observation. The data analysis technique used was the Miles and Huberman analysis technique. This study concludes that students' problem-solving and numeracy skills can be improved by implementing differentiated learning in the PBL paradigm, according to classroom action research conducted in class V-B SD Supriyadi. The results of cycles 1 and 2 showed that the average student scores increased (significantly), indicating an increase in scores. The average score of cycle 2 was 90.77 and the average score of cycle 1 was 80.00